Market Consignment Transactions and Their Legal Implications under Islamic Economic Law: Evidence from Ombilin Market - Wani, Anisa; eficandra, eficandra; Alfiander, Dodon; Arianti, Farida; Nabilah, Wardatun (UIN Mahmud Yunus Batusangkar, 2025)
This study examines the mechanisms of price determination, profit distribution, and loss management in consignment sales transactions at Ombilin Market, Nagari Simawang. The research aims to analyze how prices are set, how profits are shared, and how losses or unsold consigned goods are handled within consignment-based trading practices at the market. The research adopts a field-based qualitative approach using a descriptive method. Data were collected from both primary and secondary sources. Primary data were obtained through observations and semi-structured interviews with traders and owners of consigned goods at Ombilin Market, while secondary data were gathered from other traders and community members with knowledge of local consignment practices. Snowball sampling was employed to identify relevant informants. Data analysis was conducted by systematically describing the empirical findings and interpreting them using relevant theoretical and legal frameworks. The findings reveal that price determination is carried out through mutual agreements between traders and consigned goods owners, taking into account prevailing market prices, operational costs, and demand conditions. Profit distribution is generally based on prior agreements, whereby traders receive approximately 30–40 percent of the total profit, while the remaining share is allocated to the owners of the consigned goods. In cases of losses arising from unsold goods, several mechanisms are applied, including returning the goods to the owners, renegotiating prices through sales to wholesalers at lower rates, sharing storage-related losses, or purchasing the goods at reduced prices upon mutual consent. When consigned goods are damaged, liability rests with the owner, provided that the trader has fulfilled the obligation to report the damage. From the perspective of Sharia economic law, the implementation of consignment agreements at Ombilin Market is consistent with the principles of wakālah bi al-ujrah. Price determination practices reflect Sharia principles of fairness and economic welfare, profit distribution corresponds to agreed-upon proportions, and loss management aligns with the concept of ḍamān in Islamic economic law.